CONTRIBUIÇÕES DO SUBPROJETO PIBID/MATEMÁTICA/UFN: PERCEPÇÕES DE EGRESSOS DO PROGRAMA - Santos, Lozicler Maria Moro dos (2019)
As a starting point, this work has reflections on the contributions of the Institutional Program of the Initiation to Teaching Grant (PIBID), in relation to the teacher training of the graduates of the Mathematics course of the Franciscan University - UFN. In this sense, we try to answer the following research problem: What are the contributions of the PIBID / Mathematics / UFN subproject in the teacher training and in the professional performance of the graduates of the Mathematics course, participants in the Program? The objective of this work is to investigate the contributions of the PIBID / UFN Mathematics subproject as public policy, in the valuation of teacher education and in the professional performance of the graduates of the Undergraduate Program in Mathematics - UFN. Within the qualitative research, the case study was chosen to guide the work. In order to respond to the research problem, the contextualization of the Licenciatura degree in Mathematics - UFN, the Institutional Program of the Initiation to Teaching Grant - PIBID, and the theoretical mapping of the formation of mathematics teachers were presented. survey of the main productions in the area of limited form, around the publication in Brazil, available in CAPES Newspapers. The data were collected by means of instruments such as questionnaires, which were destined to the graduates of the degree course of Mathematics of UFN. Some categories have been identified, among them the ones that promote a teaching for freedom and autonomy: research, criticism and critical reflection on the practice, unfinished consciousness, professional competence and commitment, and conscious decision-making. From the data analysis procedure, we proceeded to analyze them, for this was adopted the Discourse Analysis. The research thesis consists in showing the contributions of the PIBID / UFN, which imply in the perceptions and experiences obtained by the participants in relation to the process of teacher education of the academic graduates of the Mathematics course. It was noticed how much the PIBID assisted in the initial formation, mainly with respect to the planning and differentiated methodologies, besides providing an interaction with the reality of the teaching work, favoring the exercise of the autonomy and the construction of the identity and teacher training, as well as as in professional performance.